Departmental distribution of respiratory mortality in older people in Córdoba, Argentina. Triennia 2000-2002 and 2015-2017 - Peranovich, Andrés Conrado; Rojas Cabrera, Eleonora Soledad; Heredia Mamani, Lina (Medicina Clínica y Social, 2022)
Introduction: In Argentina, diseases of the respiratory system are the third cause of death in the population and especially affect the elderly population. Objectives: To analyze the geographical and temporal distribution of mortality from respiratory diseases in people over 60 years of age in the province of Córdoba, Argentina, in the three-year periods 2000-2002 to 2015-2017; and investigate the relationship between this cause of death and risk factors and selected socioeconomic factors of the territory. Methodology: This is a quantitative, cross-sectional and analytical work. Cause-specific mortality rates were calculated and maps were drawn up, using Standardized Mortality Ratios (SMR), all based on official information. Linear regression models were applied to establish relationships between mortality and selected socioeconomic and risk factors. Results: Mortality rates due to respiratory causes in older people increased in almost the entire province, on average by 80% between the period 2001 and 2016, with the central area being the most affected; In addition, a significant statistical association was found between this mortality and the size of the population, the dispersed rural population, proximity to health centers, the sewage network, and overcrowding. Discussion: Respiratory mortality has increased significantly in the population of older adults in Córdoba, and this increase would not be related to the aging phenomenon itself, but to urbanization and the concentration of the population in large cities.
Keywords: ageing; mortality; social determinants of health